Pengaruh Profitabilitas dan Sistem Pengendalian Internal Terhadap Audit Delay: Studi Empiris pada Perusahaan Kosmetik yang Terdaftar di Bursa Efek Indonesia Periode 2020-2021 - Rahma Dita Fianti, Finka (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
This research aims to examine further the factors that influence audit delay. Because an audit that exceeds the statutory deadline will result in a delay in the publication of the financial report which indicates a problem in completing the audit. So, the researchers chose the title "The Influence of Profitability and Internal Control Systems on Audit Delay in cosmetics Companies Listed on the Indonesian Stock Exchange". This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange. The data used is quantitative data in the form of annual financial reports with secondary data sources.